The relationship between family functioning and juvenile delinquency at SMKN 4 Pekanbaru - Trio Saputra (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
This study aims to determine the relationship between family functioning juvenile delinquency. This study used 120 subjects students in SMK N 4 Pekanbaru, research data were collected using two scales, the scale of family function and delinquency with item number 53. Sampling in this study using non probabilitis sampling techniques, data analysis using product moment, with the help of SPSS 17.0 for Windows. Based on the analysis found that there is a negative relationship between family functioning juvenile delinquency, the correlation p = -0.590 0.000. Then the hypothesis is accepted, meaning the lower the higher the family function of juvenile delinquency and conversely the higher the lower a family function of juvenile delinquency